An Investigation into the Charge‐Storage Mechanism of MnO@Graphite as Anode for Lithium‐Ion Batteries at Low Temperature. Issue 8 (23rd April 2019) - Tian, Xiaodong; Du, Li; Yan, Yurong; Wu, Songping
Abstract: Electrochemical features and the charge‐storage mechanism of monodispersed MnO nanoparticles anchored on graphite (MnO@Graphite) for Li‐ion batteries have been investigated at a low‐temperature of −25 °C. MnO@Graphite nanocomposite rendered a remarkable reversible capacity of 456 mA h g −1 after 320 cycles under a current density of 100 mA g −1 at such a low temperature. Remarkable reversible capacity could be ascribed to the integrated structure, emergence of in‐situ formed MnO2 and hybrid pseudocapacitance. Hybrid pseudocapacitive contributions have appeared at low operational temperature, i. e., assembled heterogeneous intercalation pseudocapacitance at low potentials and surface‐controlled pseudocapacitance at high potentials. The results showed that the prepared MnO@Graphite nanocomposite is a promising candidate for Li‐ion batteries operated in harsh environment. Abstract : As cold as ice : MnO@Graphite nanocomposites are prepared. Used as anode material for lithium‐ion batteries, the composites exhibit a remarkable reversible capacity of 456 mA h g −1 after 320 cycles under a current density of 100 mA g −1 at −25 °C. Hybrid pseudocapacitive contributions, i. e., assembled heterogeneous intercalation pseudocapacitance at low potentials and surface‐controlled pseudocapacitance at high potentials have been found.